Alkaloid Profile, Anticholinesterase and Antioxidant Activities, and Sexual Propagation in Hieronymiella peruviana (Amaryllidaceae) - Olimpia Llalla-Cordova; Javier E. Ortiz; Luciana R. Tallini; Laura Torras-Claveria; Jaume Bastida; Lorena Celina Luna; Gabriela E. Feresin (Plants)
Hieronymiella peruviana, a recently described endemic species from southern Peru, belongs to the Amaryllidaceae family and is known for its diversity of alkaloids. Amaryllidoideae have been studied for their diverse biological activities, particularly for their properties in treating neurodegenerative diseases. This work examines the alkaloidal profile using GC-MS and UPLC-MS/MS of alkaloid-enriched extracts obtained from the leaves and bulbs of H. peruviana and their inhibitory activity against acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) enzymes. In addition, the phenolic and flavonoid content in the methanolic extract from bulbs was quantified and the antioxidant capacity was evaluated. Moreover, the seed germination was investigated under four temperature conditions (15, 20, 25, and 30 °C). Twenty-two alkaloids, most of them of the homolycorine- and galanthamine-type, including galanthamine, were identified in the alkaloid extracts by means of GC-MS and UPLC-MS/MS analysis. Lycorine and 8-O-Demethylhomolycorine were the most abundant alkaloids in the bulbs and leaves, respectively. The leaves and bulbs alkaloid extracts demonstrated strong AChE inhibition (IC50 = 5.20–8.60 µg/mL) and moderate BuChE inhibition (IC50 = 90.20–122.76 µg/mL). The bulbs’ methanolic extract exhibited mild antioxidant activity, showing 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) values of 16.36% at 500 μg/mL and 58.31 mg Trolox equivalents (TE)/g, respectively. Seed germination was most effective at 20 °C and 25 °C. Finally, 60 days after germination, the survival rate of H. peruviana seedlings was 48.33%. These findings establish H. peruviana as a promising source of bioactive alkaloids with potential pharmacological and therapeutic applications, as well as providing critical insights for its propagation and conservation.